Software engineering - Sommerville, Ian (International Computer Science Series, 2011)
This book discusses a comprehensive spectrum of software engineering techniques and shows how they can be applied in practical software projects. This edition features updated chapters on critical systems, project management and software requirements.
Keywords: Software : Management; Systems engineering; Dependability; Security; Software engineering; ohjelmistokehitys; tietokoneohjelmat; ohjelmistotuotanto; ohjelmistotekniikka; ohjelmointi; ohjelmointikielet; olio-ohjelmointi; tietotekniikka; tietojärjestelmät; testaus; projektit; tietoturva; systeemityö; programutveckling; datorprogram; dataprogramproduktion; programteknik; programmering; programmeringsspråk; objektorientering; informationsteknik; informationssystem; testning; projekt; datasäkerhet; systemarbete; data protection; software engineering; systems engineering; programming; software development; programming languages